Complex genomic and phenotypic characterization of the related species Staphylococcus carnosus and Staphylococcus piscifermentans - Pantůcek, R; Sedlácek, I; Doskar, J; Rosypal, S (International journal of systematic bacteriology, 1999)
On the basis of numerical analysis of 100 phenotypic features, the strains of two species, Staphylococcus carnosus and Staphylococcus piscifermentans, were differentiated into two separate phenons corresponding with the macrorestriction patterns of their genomic DNA, as well as with the results of ribotyping and PCR amplification of enterobacterial repetitive intergenic consensus sequences. One of the S. carnosus strains, the F-2 strain, was shown to be marginal, exhibiting the lowest genomic and phenotypic similarity to the S. carnosus type strain DSM 20501T. Two of the strains studied (strains S. carnosus SK 06 and S. piscifermentans SK 05) were phenotypically convergent, forming a separate phenon. They were phenotypically similar, even though the genomic DNA of one of them was homologous with that of the S. carnosus type strain, whereas that of the other was homologous with the genomic DNA of the S. piscifermentans type strain. In such cases, fingerprinting methods (particularly macrorestriction analysis and ribotyping) served as important correctives, as they allow phenotypically convergent strains to be distinguished on the basis of their genomic profiles. The results of this paper support the proposal for the new species Staphylococcus condimenti as well as the new subspecies Staphylococcus carnosus subsp. utilis.
Keywords: druhová specificita; fenotyp; polymerázová řetězová reakce; Cluster Analysis; Phenotype; Deoxyribonuclease EcoRI; Genotype; deoxyribonukleasa EcoRI; techniky typizace bakterií; restrikční mapování; Electrophoresis, Gel, Pulsed-Field; pulzní gelová elektroforéza; Restriction Mapping; ribozomální DNA; shluková analýza; Species Specificity; RNA, Ribosomal; Staphylococcus; DNA, Bacterial; DNA bakterií; RNA ribozomální; Bacterial Typing Techniques; genotyp; Polymerase Chain Reaction; DNA, Ribosomal